Synthesis and Microtubule‐Destabilizing Activity of N‐Cyclopropyl‐4‐((3, 4‐dihydroquinolin‐1(2H)‐yl)sulfonyl)benzamide and its Analogs. Issue 8 (14th November 2018) - Field, Jessica J.; Singh, A. Jonathan; Sinha, Saptarshi; Rowe, Matthew R.; Denny, William A.; Brooke, Darby G.; Miller, John H.
Abstract: While clinically useful, microtubule‐targeting agents are limited by factors that include their susceptibility to multidrug resistance. A series of aryl sulfonamides, terminally substituted with an amide or carboxylic acid, was synthesized and assayed for biological activity in two human cancer cell lines. The resulting antiproliferative activity data demonstrated that an amide was superior to a carboxylic acid in the para position. The most potent compound (3 ) had an IC50 for growth inhibition in the low micromolar range, caused cells to accumulate in G2 M of the cell cycle, and led to depolymerization of microtubules. It was also not susceptible to the P‐glycoprotein drug efflux pump that underpins the resistance of cells to long‐term drug treatment schedules. Abstract : On target : Aryl sulfonamides, terminally substituted with an amide or carboxylic acid, were synthesized and found to target a cell's microtubules. The resulting antiproliferative activity data demonstrated that an amide was superior to a carboxylic acid in the para position.